2003
DOI: 10.1046/j.1365-2761.2003.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio species isolated from diseased farmed sole, Solea senegalensis (Kaup), and evaluation of the potential virulence role of their extracellular products

Abstract: Bacteria isolated from an outbreak with moderate mortalities in farmed sole, Solea senegalensis (Kaup), in the south of Spain were identified as Vibrio harveyi and V. parahaemolyticus. Only bacterial strains showing swarming were virulent in sole and caused mortalities in experimentally inoculated fish. However, the signs of the disease were only reproduced with V. harveyi. The intramuscular inoculation of the extracellular products (ECPs) of both species produced mortalities in inoculated fish and the appeara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(99 citation statements)
references
References 22 publications
4
92
1
1
Order By: Relevance
“…The gross external lesions described in the common nase (L S 407 to 437 mm, W 670 to 760 g) and chub (L S 97 to 158 mm, W 15.7 to 85.7 g) corresponded to the description of similar lesions in other fishes infected by other Vibrio species. For infections with V. anguillarum, this was documented by Anderson and Conroy (1970) (erythema at the base of the fins, around the vent and within the mouth), for infections with V. pelagius (haemorrhages at the base of the fins) by Angulo et al (1992), for infection with V. salmonicida (haemorrhages evident around the abdomen) by Holm et al (1985), for infection with V. splendidus (haemorrhages in the mouth and base of the fins) by Lupiani et al (1989) and Angulo et al (1994), and for infection with V. harveyi (haemorrhages in the vicinity of the mouth and fins) these were described by Zorrilla et al (2003). Eye lesions (exophthalmia, corneal opaques) were described in cases of vibriosis caused by V. alginolyticus (Lee 1995), V. harveyi (Hispano et al 1997) and V. anguillarum (Anderson and Conroy 1970).…”
Section: Discussionmentioning
confidence: 99%
“…The gross external lesions described in the common nase (L S 407 to 437 mm, W 670 to 760 g) and chub (L S 97 to 158 mm, W 15.7 to 85.7 g) corresponded to the description of similar lesions in other fishes infected by other Vibrio species. For infections with V. anguillarum, this was documented by Anderson and Conroy (1970) (erythema at the base of the fins, around the vent and within the mouth), for infections with V. pelagius (haemorrhages at the base of the fins) by Angulo et al (1992), for infection with V. salmonicida (haemorrhages evident around the abdomen) by Holm et al (1985), for infection with V. splendidus (haemorrhages in the mouth and base of the fins) by Lupiani et al (1989) and Angulo et al (1994), and for infection with V. harveyi (haemorrhages in the vicinity of the mouth and fins) these were described by Zorrilla et al (2003). Eye lesions (exophthalmia, corneal opaques) were described in cases of vibriosis caused by V. alginolyticus (Lee 1995), V. harveyi (Hispano et al 1997) and V. anguillarum (Anderson and Conroy 1970).…”
Section: Discussionmentioning
confidence: 99%
“…V. harveyi ECPs are well known for their capacity to induce lysis of connective tissue. For example, Zorrilla et al (2003) evaluated the potential virulence role of V. harveyi and V. parahemolyticus extracellular products and reported that tissue lysis and ulcers were only seen on the surface of the fish after inoculation with ECPs from V. harveyi. Similarly, Zhang & Austin (2000) demonstrated that the most pathogenic isolate of V. harveyi to salmonids produced ECPs with a maximum effect on fish tissues.…”
Section: Discussionmentioning
confidence: 99%
“…En ese sentido, se ha reportado a V. alginolyticus como el causante de enfermedades en organismos acuáticos cultivados (Gómez-León et al, 2005, Martins et al 2010, especialmente en los estadios iniciales de vida (Zorrilla et al 2003) produciendo septicemia, hemorragias, úlceras a nivel epitelial con necrotización progresiva (Gómez-León et al 2005) y acumulación de líquido ascítico en la cavidad peritoneal (Paperna 1984). A consecuencia de ello, el uso de antibióticos tradicionales ha sido la estrategia más aplicada contra las infecciones bacterianas, pero su uso indiscriminado ha originado la aparición de bacterias multidrogo resistentes, lo que ha conllevado en muchas ocasiones, al desarrollo de patologías que no pueden ser tratadas con antibióticos convencionales e incluso al desarrollo de cepas bacterianas resistentes que pueden infectar a otros organismos, incluyendo al hombre (Defoirdt et al 2007).…”
Section: Introductionunclassified